Clever manipulations 2

Algebra Level 3

Suppose that p , q p,q and r r are the roots of x 3 2 x 2 + 2 x 4 x^3-2x^2+2x-4 . Find the value of the product

( p 2 + q + r ) ( q 2 + p + r ) ( r 2 + p + q ) (p^2+q+r)(q^2+p+r)(r^2+p+q)


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Tom Zhou
Oct 3, 2014

There are two key insights to this problem. Firstly, notice that p + q + r = 2 p+q+r=2 by Vieta or q + r = 2 p q+r=2-p . Thus p 2 + q + r = p 2 p + 2 p^2+q+r=p^2-p+2 . Doing similarly for the other two, we get the desired product as

( p 2 p + 2 ) ( q 2 q + 2 ) ( r 2 r + 2 ) (p^2-p+2)(q^2-q+2)(r^2-r+2)

The second clever idea is to note that since p p is a root, then p 3 2 p 2 + 2 p 4 = 0 p^3-2p^2+2p-4=0 or p 3 = 2 p 2 2 p + 4 p^3=2p^2-2p+4 and thus p 2 p + 2 = p 3 2 p^2-p+2=\frac{p^3}{2} . Doing similarly for the other two, the product is

( p 3 ) ( q 3 ) ( r 3 ) 2 3 \frac{(p^3)(q^3)(r^3)}{2^3}

and since p q r = 4 pqr=4 by Vieta, the answer is

4 3 2 3 = 8 \frac{4^3}{2^3}=\boxed{8}

I noticed the first one but missed the second!!

Adarsh Kumar - 6 years, 7 months ago
U Z
Oct 17, 2014

f ( x ) = x 2 ( x 2 ) + 2 ( x 2 ) f(x) = x^{2}(x - 2) + 2(x - 2)

f ( x ) = ( x 2 ) ( x 2 + 2 ) f(x)= (x - 2)( x^{2} + 2)

f ( x ) = 0 , x = 2 , x 2 = 2 f(x) = 0 , x = 2 , x^{2} = -2

t h e n p = 2 , q = i 2 , r = i 2 then p = 2 , q = i \sqrt {2} , r = - i \sqrt{2}

thus kepping the values we get answer as 8

i did the same way

will jain - 6 years, 7 months ago

i did it the same way as u did , but i had problem understanding the part regarding the root of -2, which theoretically is an imaginary number. could u please explain it to me???

A Former Brilliant Member - 6 years, 7 months ago

Log in to reply

here it is not said that all the roots are real

since there are three roots we have to take all of them into consideration

U Z - 6 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...